Post-marketing surveilance study of creatine-guanidinoacetic acid safety in healthy adults - Ranisavljev, Marijana; Todorovic, Nikola; Stajer, Valdemar; Ostojic, Sergej M. (Frontiers in Nutrition, 2024)
A post-marketing surveillance study assessed the adverse events and possible risk of elevated homocysteine levels after the supplementation with creatine-guanidinoacetic acid mixture in apparently healthy adults. The participants were recruited through social media platforms and online discussion boards, with side effects and total plasma homocysteine (T-Hcy) levels evaluated regularly during a supplementation period of six months. Thirthy eight individuals (n = 38, 34.2% female) completed the evaluation period and were included in the final analyses. Serious side effects were absent. Two participants (5.3%) reported transitional nausea during the introductory weeks of the supplementation; no participants stopped the treatment. Baseline T-Hcy levels were 11.6 ± 3.1 µmol/L (95% confidence interval [CI], from 10.6 to 12.6). The intervention induced a mild reduction in T-Hcy levels across the monitoring period (P = 0.028), with T-Hcy levels after one, two, three, and six months were 10.4 ± 3.0 µmol/L, 10.6 ± 2.9 µmol/L, 10.1 ± 2.7 µmol/L, and 9.3 ± 2.8 µmol/L, respectively. These findings suggest the overall tolerability of creatine-guanidinoacetic mixture in healthy adults, with homocysteineincreasing risk of no concern.